Optimization of DD-110 Neutron Generator Output for Boron Neutron Capture Therapy Using Monte Carlo Simulation - Hossam Donya; Muhammed Umer (Quantum Beam Science)
Boron neutron capture therapy (BNCT) is a specialized cancer treatment that leverages the high absorption cross-section of boron for thermal neutrons. When boron captures neutrons, it undergoes a nuclear reaction that produces alpha particles and lithium ions, which have high linear energy transfer (LET) and can effectively damage nearby cancer cells while minimizing harm to surrounding healthy tissues. This targeted approach makes BNCT particularly advantageous for treating tumors situated in sensitive areas where traditional radiation therapies may pose risks to critical structures. In this study, the deuterium–deuterium (DD) neutron generator, specifically the DD-110 model (neutron yield Y = 1 × 1010 n/s), served as the neutron source for BNCT. The fast neutrons produced by this generator were thermalized to the epithermal energy range using a beam-shaping assembly (BSA). The BSA was designed with a moderator composed of 32 cm of MgF2, a reflector made of 76 cm of Pb, and filters including 3 cm of Pb and 1.52 cm of Bi. A collimator, featuring a 10 cm high Pb cone frustum with a 12 cm aperture diameter, was also employed to optimize beam characteristics. The entire system’s performance was modeled and simulated using the MCNPX code, focusing on parameters both in-air and in-phantom to evaluate its efficacy. The findings indicated that the BSA configuration yielded an optimal thermal-to-epithermal flux ratio (<semantics>φther</semantics>/<semantics>φepth</semantics>) of 0.19, a current-to-flux ratio of 0.87, and a gamma dose-to-epithermal flux ratio of 1.71 × 10−13 Gy/cm2, all aligning with IAEA recommendations. The simulated system showed acceptable ratios for <semantics>φther</semantics>/<semantics>φepth</semantics>, gamma dose to epithermal flux, and beam collimation. Notably, the advantage depth was recorded at 5.5 cm, with an advantage ratio of 2.29 and an advantage depth dose rate of 4.1 × 10−4 Gy.Eq/min. The epithermal neutron flux of D110 exceeded D109, but D110’s fast neutron contamination increased ~6.6 times. On the other hand, D110’s gamma contamination decreased by 30%. Based on these findings, optimizing neutron source characteristics is crucial for BNCT efficacy. Future research should focus on developing advanced neutron generators that balance these factors, aiming to produce optimal neutron yields for enhanced treatment outcomes and broader applicability.